Latin American Growth : A Trade Perspective - de la Torre, Augusto; Ize, Alain (World Bank, Washington, DC, 2019)
This paper reviews the determinants of Latin America's uneven growth based on an accounting decomposition that breaks down countries' growth (relative to the world) into three trade-related channels: (i) an export pull measuring the traction exerted by the country's exports, (ii) an external leverage measuring the impact of the country's use of external resources, and (iii) a domestic response measuring the impact of the country's imports on its domestic income. This decomposition brings to light three regional growth dynamics: the first is centered on commodities and South America, the second on manufactures and Mexico, and the third on services and Central America. The evidence points toward the need for a trade-oriented growth agenda that puts a premium on raising exports and making countries more attractive to people, not just capital. The latter in turn adds urgency to healing the region’s social fractures and dealing with its institutional weaknesses.